Dampak Kondisi Sosial Ekonomi, Respon Kebijakan Pemerintah Dan Pengaruhnya Terhadap Keberlanjutan Ukm Dan Kinerja Keuangan - Rakhmawati, Antin; Rahardjo, Kusdi; Prakasa, Yudha; Nizar, Muhammad (Akademi Sekretari Manajemen Taruna Bakti, 2023)
This study aims to examine the impact of socio-economic conditions in the aftermath of the COVID-19 pandemic, government policy response on the sustainability and performance of small businesses. This research was conducted on leading sector small businesses in Malang City. Leading business sectors in Malang City include the craft sector, the fashion sector, the food and beverage sector, the application sector and the film and animation design sector. The population of the leading sector small businesses in the city of Malang is 356 business units. The sampling technique in this study is probability sampling with proportional random sampling method. The inferential statistical analysis used is Partial Least Square (PLS) using the smartPLS 3 statistical application. The results of this study indicate that the socio-economic and government policy response variables have a significant positive effect on SME sustainability, then the SME sustainability variable has a significant positive effect on financial performance